Joint control of power and rates of wireless networks based on Nash game. (2016) - Kong, Shulan; Chen, Wen
This paper proposes a distributed joint control of power and rate for a wireless network where two master nodes are operating at same time. The control problem of joint power and rates is formulated using Nash game technique that is stochastic linear-quadratic Gaussian and has a non-zero sum. In the considered wireless network, the two active master nodes have access only to noise-corrupted measurements of the power and rates. When each master node uses a linear Kalman-filter-like state estimator and when a one-step delayed output and a one-step delayed control input of the power and rates are given, an optimal and joint strategy for control of each master node's power and rates is presented. The optimal controllers of the two nodes for the closed-loop Nash equilibrium solution are interrelated and cannot be determined separately. They demonstrate a cooperative and influential relationship between the operating master nodes.